Japanese slang : - Hindaichi, Haruhiko (Yenbooks, 1994)
This book reveals in vivid detail the richness of Japanese slang in all its amusing, bizarre, and shocking forms. Thoroughly researched and comprehensive in its coverage, JAPANESE SLANG traces the origins of these expressions and explains the ingo, or hidden words, used by thieves, prostitutes, Buddhist monks, pickpockets, sushi chefs, and other colourful characters.